Cultural models of risk - the multiple meanings of living in the world of dangerous possibilities - Kamppinen, Matti (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 1997)
One of the contributions of cultural studies in risk and technology assessment is to emphasise the importance of cultural models and to show how cultural models of risk are best studied by means of ethnographic case studies. In this article I shall first explicate the conceptual background and then proceed to present two case studies that illuminate my line of argument, one from Western Finland, and one from the Peruvian Amazon. Finally I will discuss some systematic connections between the risk profile of late modernity and the risks from the "archaic" Amazonian case study.